STM32-BASED FORMULA STUDENT RACE CAR VEHICLE CONTROL UNIT, SHUTDOWN CIRCUIT, CAN BUS COMMUNICATION - Dildabek, Yessenkhan (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The Formula Student is an international competition aimed at enhancing engineering culture among a new generation of engineers by conducting competitions in the form of formula-type race car designs. The "NU Motorsports" club of Nazarbayev University aims to develop the first electric formula-type race car in the framework of this competition. As a senior engineer of the Grounded Low Voltage department of the club, the main goal of the current project is to develop a functional control unit that abides by all regulations of the competition. Specifically, the objective is to develop a custom VCU board that will control the inverter and be capable of running necessary algorithms pertaining to the motion of the car. Moreover, as adjacent systems of the VCU, the project goes through the implementation of the Accelerator Pedal Position Sensor (APPS), Shutdown interface circuit, and the design of a communication bus between different control units. Specifically, the given work discusses the realization of the Controller Area Network (CAN) compatible with the inverter.
Keywords: Formula Student; Formula SAE; Formula Student Electic; Electric Vehicle; Inverter; Vehicle Control Unit; VCU; Shutdown Circuit; CAN bus; Controller Area Network; Control Logic; Finite State Machine; Embedded Systems; STM32; Microcontroller; MCU; type of access: restricted access